Melting features and viscosity of SiO2-CaO-MgO-Al2O3-FeO nickel slag in laterite metallurgy - Pan C.; Lv X.; Bai C.; Liu X.; Li D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Physic-chemical properties of slag at high temperature were very important for the production of ferronickel alloy by pyrometallurgical process. It determines the operation efficiency, metal recovery ratio, energy consumption and the distribution of elements (like S and P) between the slag and metal. In the present work, the effect of slag basicity on melting features and viscosity of the slag was investigated. The basicity of the SiO2-CaO-MgO-Al2O3-FeO quinary slag system varied from 0.76 to 0.99. The results showed that: 1) all the slag samples began to soften at the same temperature; 2) the softening temperature, melting temperature and flowing temperature decreased with the increase of basicity from 0.76 to 0.92, after that, the temperatures would increase sharply. 3) the inflection point temperature of viscosity-temperature curve became larger and larger with the increase of basicity within 0.76 ~ 0.99.